Labor market and poverty in Brazil - Ricardo Paes de Barros; Carlos Henrique Corseuil; Phillippe G. Leite (Institute for Applied Economic Research (ipea), 2015)
This paper investigates if the responsibility of the poverty level registered in Brazil is the poor operation of the labor market, in terms of underremuneration and underutilization of the labor factor. By means of a microsimulation based decomposition of distributional changes we assess the impact on the degree of poverty of unemployment, segmentation, and discrimination. In order to estimate the effect of these labor market imperfections on poverty, it was necessary, first, to define precisely the concepts of unemployment, segmentation and discrimination. Secondly, it was necessary to define how an ideal situation where human resources are properly used and remunerated would look like, given the prevailing macroeconomic conditions. It was found that, if the conditions of the average segment of the Brazilian labor market were extended to all segments, the effect on poverty would not be very significant (the average income gap would drop from the observed 12.1% to 9,6%). Even if this condition were extended only to those below the mean, the effect on poverty would not be so higher (P1 would drop to 8,1%). Among the items of the effect of underremuneration and underutilization of labor, it is worth mentioning that the effect of unemployment is extremely limited in absolute terms, although in relative terms it is the major effect on poverty.
Keywords: 330